A COMPARISON OF TWO PROTOCOLS OF INTRAVAGINAL MISOPROSTOL FOR SECOND TRIMESTRER MEDICAL TERMINATION OF PREGNANCY - Fatima, Yasmin; Akhtar, Shahida (Pakistan Armed Forces Medical Journal, 2011)
Objective: To compare the efficacy and side effect profiles of two different dosage protocols of intra-vaginal misoprostol. Study Design: Randomized control trial. Place and Duration of Study: Department of Gynaecology and Obstetrics, Combined Military Hospital, Rawalpindi, from May 2006 to December 2006. Material and Methods: A total of 128 womens, aged 18-40 years, planned for 2nd trimester pregnancy termination, were randomly assigned to two groups of 64 each. Group – I women received vaginal misoprostol 400ug three hourly for a maximum of 8 doses in 24 hours. Women in group-II received vaginal misoprostol 400ug six hourly for a maximum of four doses in 24 hours. If abortion did not occur in 24 hours, the same regimens were repeated. Without succesful abortion in 48 hours, misoprostol administration was abandoned in favour of surgical induction. Results: The median induction to abortion interval in group – I (14.4 hours) was shorter than in group – II (18.2) (p< 0.001). The frequency of fever was more common in group – I (p = 0.01). The pregnancy related symptoms decreased in both groups after misoprostol and decrease in breast tenderness was most marked two to three hours after administration. Misoprostol induced fever was seen at least five hours after administration in up to 37.5% women, this peak being slightly higher and occurring earlier in group – I than in group – II. Lower abdominal pain peaked after three to four hours in group – I and after five to six hours in group – II, with no significant difference in pain intensity or analgesic requirements. Other common side effect were diarrhea followed by nausea and vomiting in both the groups. Conclusion: Protocol of 400ug misoprostol administered 6 hourly / 24 hours is more effective in reducing induction – abortion interval and inducing successful abortion within 48 hours without any major increase in side effects.